Pemberdayaan Masyarakat Melalui Pelatihan Ecoprint Daun Mangrove (Sonneratia alba) Dengan Teknik Pounding Di Pulau Maitara Kota Tidore Kepulauan - Abubakar, Salim; Aris, Muhammad; Subur, Riyadi; Iksan, Kusdi Hi; Wahidin, Nurhalis; Irham; Ahmad, Aditiyawan; Najamuddin; Achmad, M. Janib; Muksin, Darmiyati; Susanto, Adi Noman (Universitas Mataram, 2024)
Mangrove plants can be used as natural dyes to replace synthetic dyes. One part of the mangrove plant that has the potential to be used is the leaves. Sonneratia sp is a type of mangrove that can be used as a raw material in making ecoprints, where the results of this type of ecoprint leave a light green trail with an even shape. All parts of the mangrove plant can be used as a coloring material for ecoprint products with the pounding method. The objectives of the PKM activity are: partners can learn about the benefits of Sonneratia alba mangrove leaves as raw materials for ecoprints, empowering the community in increasing innovative creativity through making ecoprints, applying Sonneratia alba mangrove leaf ecoprint making technology with the pounding method and getting quality ecoprint product motifs. The activity method carried out in the ecoprint making training is carried out through several stages, namely field surveys/observations, counseling and training. The results of the PKM provide knowledge about the benefits of Sonneratia alba mangrove leaves as raw materials for making ecoprint products and increasing creativity in making ecoprints with the pounding technique. This ecoprint training activity is not only for education or knowledge, but can also help improve the economy, this training activity gets positive value and support from the Maitara Island community, especially for the managers of the Ngusulenge mangrove tourism object, Maitara Tengah Village. This activity is a trigger to be more enthusiastic about working to utilize natural resources, especially mangrove forests. Ecoprint products are expected to be one of the typical souvenirs of Maitara Island and the ecoprint products produced are bags, tablecloths, handkerchiefs and headscarves.